To Detection of Fish Disease using Augmented Reality and Image Processing - Chakravorty, Hitesh (European Journal of Applied Sciences, 2020)
Fish mortality due to diseases. The diseased identification at early stage to prevent and spreading of diseases. The image processing technique is already existed to detect fish disease. The Augmented model and Image Processing a new approach to detect fish disease using smart phone.The comparison of the disease fish on the spot is not possible in image processing technique. The AR model technique has over come on the spot identification of disease fish. Taken one Epizootic Ulcerative Syndrome (EUS) diseased fish model for the proposed approach.The images taken with the AR model for image processin HSV operation for better accuracy to diseased area detection.